INFLUENCE OF PLASMA NITRIDING ON SURFACE ROUGHNESS OF STEELS - M. S. Ahmed; A. N. Drobov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The research results of the influence of plasma at different levels of surface roughness are presented. The objective of this work is to determine the effects of plasma after the treatment for instrument steel 40Cr and construction steel 38H2MYUA.